The Effects of the Socialization of Physical Education Teachers on Their Modes of Interaction With Students in Tunisian Schools - Nasri, Bechir; Kadri, Abdelmotaleb; Souissi, Nizar; Rouissi, Mourad (Frontiers in Sociology, 2022)
This article uses an interactionist perspective to address the socialization of physical education teachers in a teaching setting in Tunisia. The two main objectives of the study are to present the social characteristics of the population studied, draw general conclusions about the social origins of the Tunisian teachers of physical education and sport, and to identify the link between socialization and the pedagogical practice of physical education teachers in Tunisian schools. My colleagues and I collected data through participant observations and in-depth interviews with a representative sample of teachers. The results show that the socio-cultural origin, the type of training and the generational effect of physical education teachers in a teaching setting in Tunisian schools influence pedagogical behavior.